2015
DOI: 10.1016/j.addr.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of oligonucleotides with lipid nanoparticles

Abstract: Since their inception in the 1980's, oligonucleotide-based (ON-based) therapeutics have been recognized as powerful tools that can treat a broad spectrum of diseases. The discoveries of novel regulatory methods of gene expression with diverse mechanisms of action are still driving the development of novel ON-based therapeutics. Difficulties in the delivery of this class of therapeutics hinder their in vivo applications, which forces drug delivery systems to be a prerequisite for clinical translation. This revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
121
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(122 citation statements)
references
References 124 publications
(121 reference statements)
1
121
0
Order By: Relevance
“…1) As a cargo of these NPs, small-interfering RNAs (siRNAs) are frequently adopted as an effective strategy for cancer treatment due to their suppression of cancerrelated gene (e.g., c-Myc) expression.…”
mentioning
confidence: 99%
“…1) As a cargo of these NPs, small-interfering RNAs (siRNAs) are frequently adopted as an effective strategy for cancer treatment due to their suppression of cancerrelated gene (e.g., c-Myc) expression.…”
mentioning
confidence: 99%
“…117,118 This strategy, although does not ensure an outstanding preservation, is highly versatile and suitable for these purposes. For instance, there have been reported successful nonviral siRNAs deliveries with other systems like polymers, 119,120 peptides, 121 dendrimers, 122 lipids, 123 or metallic nanoparticles 124 among many other systems. 125,126 In fact, the use of hybrid carriers containing polycationic fragments also enables the combination of features from both components.…”
Section: Surface Deposition Of Nucleic Acids Onto Msns For Gene Transmentioning
confidence: 99%
“…Various in vivo studies indicated that cationic liposomes show fast serum clearance and adsorption of anionic serum proteins on them, which cause early release of therapeutics. Surface coating of cationic liposomes with PEG (polyethylene glycol) demonstrated better colloidal stability and extended blood circulation half-life 20 . Although cationic lipids have higher encapsulation efficiency, their use as a delivery vehicle is limited because they are cytotoxic in nature.…”
Section: Liposomesmentioning
confidence: 99%
“…(ii) Formation of ion-pairs with cationic lipids due to the diffusion of anionic lipids of the cell membrane into the cationic lipoplexes. (iii) Displacement by anionic lipids and release of As-ODNs into the cytoplasm 20,21 . In vitro studies were performed on G6 glioma cell line.…”
Section: Liposomesmentioning
confidence: 99%